Predictors of Mental Health Care Utilization in Veterans With Post-Traumatic Stress Disorder Symptoms and Hazardous Drinking. Issue 10 (1st October 2016) - Johnson, Emily M.; Barrie, Kimberly A.; Possemato, Kyle; Wade, Michael; Eaker, April; Ouimette, Paige C.
ABSTRACT: Objectives: Describe outpatient mental health service use in a sample of recent combat Veterans with post-traumatic stress disorder (PTSD) symptoms and hazardous alcohol use and investigate predictors of mental health care utilization. Methods: In this prospective study, 126 Veterans with full or subthreshold PTSD and hazardous alcohol use completed a baseline assessment and reported mental health service use through a 12-month follow-up period. Logistic regressions were used to identify factors predicting mental health care utilization. Results: Veterans who were employed were 63% less likely to use outpatient mental health care in the 12 months following baseline. Additionally, for each 1-point increase in negative mental health care beliefs, participants were 70% less likely to use outpatient mental health care. For each 1-point worsening in social support and leisure functioning, participants were 2.2 times more likely to use outpatient mental health care. Conclusions: The current study indicates that negative mental health beliefs are barriers to mental health care while unemployment and poor social support/leisure functioning are predictors of mental health care utilization for recent combat Veterans with PTSD symptoms and hazardous alcohol use. Patient and system level interventions for these factors are discussed to guide efforts to improve mental health care among this high-need population.